Molecular and isotope chronostratigraphy of tertiary source rocks and crude oils - Eiserbeck, Christiane (Curtin University, 2011)
The exploration and production of petroleum from the subsurface is an important sector of industry to maintain the standards of our modern life. The availability of these natural resources has diminished in the past decades while the demand for their industrial products such as fuel or plastics is gradually increasing. Thus, there is a pressing need for effective and efficient techniques that improve future petroleum exploration strategies. The age of an oil is one of the most important parameters for oil‐source and oil‐oil correlations in order to understand petroleum systems. Currently, the determination of an oil’s age is preceded by drilling a petroleum exploration well. Such a well is associated with substantial costs as well as environmental impacts adding an economical and conservational side to the problem.Existing geochemical methods based on source‐ and age‐specific biomarker ratios, such as the C28/C29 steranes or the abundance of n‐alkanes nC15, nC17, nC19, often limit the age information to a minimum or maximum age of the sample. Therefore, establishing the age of an oil based on its geochemical characteristics in higher resolution has high economical and environmental sustainability value.Petroleum geochemistry is one of the central disciplines involved in understanding petroleum systems, the processes and factors influencing the generation, quality and quantity of petroleum. It involves the application of organic geochemical tools such as biomarker analysis and stable isotopic measurements to study the origin, formation, migration, accumulation and alteration of organic components.In this research, important concepts and novel techniques of petroleum geochemistry have been applied to develop a geochemical tool for high resolution age estimation of crude oils and source rocks.The analysis of biomarkers (molecular fossils) in petroleum enables one to reconstruct the source organic matter, the depositional environment and the alteration processes (e.g. diagenesis, biodegradation, water‐washing and migration‐contamination). More importantly, biomarkers that are specifically derived from only one organism can carry valuable information about the age of the organic matter that generated the petroleum. Additional compound specific isotope data can support the age information.During the Tertiary – about 65 ‐ 2 million years (Ma) ago – flowering plants (angiosperms) proliferated and diversified, although they originated in the Cretaceous. Thus, increasing abundances of angiosperm biomarkers such as oleanoids, lupanoids and ursanoids in crude oils or source rocks indicate source organic matter of Cretaceous to Tertiary age. Age predictions based on biomarker distributions have been studied in the past. However, the resolution of these estimations has been low and requires improvement. Furthermore, absence of these biomarkers does not exclude Cretaceous to Tertiary age.The aim of this study was to establish a robust geochemical tool for high resolution age estimation of Tertiary crude oils and source rocks based on the molecular and stable isotopic distribution of higher plant biomarkers. A set of Tertiary oils and source rocks from the Arctic, Southeast Asia and California was assembled. The selected source rock samples were chosen as a learning set to elucidate biomarker‐age relationships, based on their well defined biostratigraphy and age. All samples were analysed for their higher plant biomarker composition as well as for additional molecular signals indicative of the thermal maturity and biodegradation of these samples.Significant challenges are involved in the detailed assessment of higher plant contribution to sedimentary organic matter. This is due to the broad suite of diagenetic products and stereochemical and structural isomers that exist within the group of angiosperm biomarkers, their almost identical behaviour on gas chromatographic columns and their similar mass spectral characteristics. A number of sophisticated chromatographic separation techniques were applied and chromatographic methods developed in order to resolve these co‐elution problems including gas chromatography‐mass spectrometry (GC‐MS), metastable reaction monitoring (GC‐MRM‐MS) and comprehensive twodimensional gas chromatography (GCxGC).In Chapter 2 for the first time the separation of the most commonly applied angiosperm biomarkers 18α(H)‐oleanane, 18β(H)‐oleanane and lupane is reported. This was achieved by developing a suitable and powerful GCxGC method. Molecular ratios, such as the oleanane index, were commonly used in the past to indicate higher plant input and also as a proxy for thermal maturity. However, the co‐elution of lupane with the oleanane isomers on regular nonpolar gas chromatographic columns was overlooked. The presence of lupane in many geological samples from the Tertiary was only acknowledged recently due to its very similar retention time and mass spectrum. To date, no analytical method allowed the separation of all three components in a single analysis. GCxGC coupled with a time‐of‐flight mass spectrometer (GCxGC‐TOFMS) provides the resolution power to separate all three biomarkers in a complex mixture such as petroleum in both the first and the second dimension of separation. Moreover, this separation was achieved by analysing the whole oil. No further laboratory separation procedures were required prior to the chromatographic analysis.Thermodynamic calculations of the three‐dimensional structures of 18α(H)‐ and 18β(H)‐oleanane illustrate a possible explanation for the subtle differences in interaction with the two orthogonal phases of the chromatographic columns due to steric differences.The successful application of GCxGC was extended to a broad range of higher plant biomarkers. Chapter 3 presents a comprehensive study of the separation of an array of higher plant biomarkers by different analytical techniques (GCMS, GC‐MRM‐MS, GCxGC‐TOFMS and GCxGC‐FID). Comparison of the resolving power of these techniques proved GCxGC to be superior and an ideal tool for petroleum geochemistry.As a result, different diagenetic products of higher plant derived biolipids, such as saturated (e.g. oleanane and lupane) and unsaturated pentacyclic (e.g. oleanenes), ring A‐degraded and aromatised compounds were identified. Known co‐elution problems such as the co‐elution of 24‐norlupane and norhopane were resolved, and previously unknown occurrences of co‐elution using 1D GC systems were revealed.Of particular importance is the separation achieved in the second dimension for compounds having identical molecular masses and mass spectral fragmentation patterns. Co‐elution of such compounds could not have been resolved by using extracted ion chromatograms from 1D GC‐MS analysis. The identification, quantification and acquisition of their uncontaminated mass spectra were impossible. Comparison of the thermal maturity parameter C32 homohopane S/(S+R) confirmed the comparability of parameters derived from GCxGC analysis with those obtained in the past using 1D GC techniques. Consequently, GCxGC can be routinely applied for fingerprinting and detailed characterisation of petroleum, improving oil‐source and oil‐oil correlation studies. The enhanced resolution and sensitivity of important higher plant biomarkers improves our understanding of diagenetic and catagenetic pathways, and alteration processes in the subsurface.Ultimately, the age estimation of Tertiary crude oils could be improved to within 10 Ma (Chapter 4). This is the highest resolution of molecular chronostratigraphy ever reported. An extended angiosperm‐gymnosperm‐index (AGI) was developed, comprised of the ratio of many saturated and aromatic angiosperm to gymnosperm biomarkers. Using the learning sample set of rocks, a relationship of the AGI to age was established that can be used to calculate the ages of crude oils. The validity of this tool was confirmed by comparing the calculated ages with the age ranges determined prior to this study by oil‐source correlation.Furthermore, the offsets between the stable isotopic composition (carbon and hydrogen) of the isoprenoids pristane (Pr) and phytane (Ph), determined as δ13C (Ph‐Pr) and δD (Ph‐Pr), respectively, support the established molecular age correlation and respond to major climatic and tectonic events during the Tertiary. The substantial decrease in both δ13C and δD in the Early Eocene can be attributed to the Paleocene‐Eocene Thermal Maximum (PETM), one of the most dramatic global warming events in the geological record. The release of massive amounts of isotopically light methane from the melting of gas hydrates is reflected in the low δ13C value of Ph. The freshwater environment in the Arctic Gulf during the Early and Mid‐Tertiary resulted in a depleted stable hydrogen isotope composition of Ph, maximising during the PETM, when no ice caps existed and the melting gas hydrates introduced additional freshwater to the oceans.The improved separation of age‐diagnostic angiosperm‐biomarkers presented in this study extends our knowledge of their biological precursors and diagenetic and catagenetic formation pathways. Moreover, the advanced analytical capacity of GCxGC can be applied to many other geochemical problems to revolutionise the analytical tool box of organic geochemistry.These findings will help further develop our understanding of the geochemical processes that influence the nature, abundance and distribution of petroleum hydrocarbons in sedimentary basins and should contribute significantly to improving the effectiveness and efficiency of petroleum exploration.